Granulomatosis with polyangiitis mimicking infective endocarditis in an adolescent male. Issue 9 (September 2016) - Varnier, Giulia; Sebire, Neil; Christov, Georgi; Eleftheriou, Despina; Brogan, Paul
Abstract Granulomatosis with polyangiitis (GPA) is a rare but serious small vessel vasculitis with heterogeneous clinical presentation ranging from mainly localised disease with a chronic course, to a florid, acute small vessel vasculitic form characterised by severe pulmonary haemorrhage and/or rapidly progressive vasculitis or other severe systemic vasculitic manifestations. Cardiac involvement is, however, uncommon in the paediatric population. We report a case of a 16-year-old male who presented with peripheral gangrene and vegetation with unusual location on the supporting apparatus of the tricuspid valve, initially considered to have infective endocarditis but ultimately diagnosed with GPA. We provide an overview of the limited literature relating to cardiac involvement in GPA, and the diagnostic challenge relating to infective endocarditis in this context, especially focusing on the interpretation of the antineutrophil cytoplasmic antibody (ANCA) and the characteristic clinical features to identify in order to promptly recognise GPA, since timely diagnosis and treatment are essential for this potentially life-threatening condition.